The Importance of Hiring Frictions in Business Cycles - Renato Faccini; Eran Yashiv (Institute of Labor Economics (IZA), 2020)
Hiring is a costly activity reflecting firms' investment in their workers. Micro-data shows that hiring costs involve production disruption. Thus, cyclical fluctuations in the value of output, induced by price frictions, have consequences for the optimal allocation of hiring activities. We outline a mechanism based on cyclical markup fluctuations, placing emphasis on hiring frictions interacting with price frictions. This mechanism generates strong propagation and amplification of all key macroeconomic variables in response to technology shocks and mutes the traditional transmission of monetary policy shocks. A local projection analysis of aggregate U.S. data shows that the empirical results, including the cyclicality of markups, are consistent with the model's impulse response functions.
Keywords: E22; E24; E32; E52; 330; hiring as investment; intertemporal allocation; business cycles; confluence of hiring and price frictions; propagation and amplification; mark up cyclicality